外傷性神経腫を合併した再発性舌扁平上皮癌の1例 - 篠崎, 勝美; 木原, 俊之; 楠川, 仁悟; 岩永, 譲; 宮園, 佳宏; 岩本, 修 (日本口腔外科学会雑誌, 2014)
Traumatic neuroma is a benign, hyperplastic tumor caused by neuron deformation. We report the case of a traumatic neuroma developing in the deeper portion of a recurrent tongue carcinoma that was misinterpreted to be deep invasion of the cancer. A 65-year-old woman was referred to our hospital because of ulcer formation in the left side of the tongue. In the past history, she had received partial resection of the left side of the tongue for squamous cell carcinoma (SCC) at 54 years of age. Clinical examination of the tumor showed localized induration in the superficial layer of the tongue. However, contrast magnetic resonance (MR) images showed that the lesion extended to near the lingual septum. Because well-differentiated SCC was diagnosed on biopsy, hemiglossectomy of the mobile tongue was performed. Postoperative histological examination of the resected tongue specimens revealed neuroma tissue in the deep part of the tongue. In contrast to the MR image findings, the SCC tissue was found in only the superficial layer of the tongue. Consequently, traumatic neuroma, that was apparently coused by surgical intervention during the previous tongue cancer operation, made it difficult for us to determine the tumor extent preoperatively. No recurrence has occurred after 2 years of postoperative follow-up.